Automatic Irrigation System using Wireless Control - Muhammad Razif, Muhammad Rusydi; Ravindran, Preetharan; Mohd Nordin, Ili Najaa Aimi; Zulkifli, Nor Saradatul Akmar (ELEKTRIKA- Journal of Electrical Engineering, 2019)
Traditional methods of irrigation and fertilizing is very time consuming for farmers. Over-irrigation as well as leaching of fertilizers below the root zone, erosion, and transport of soil and chemical particles to the drainage ditches can increase energy and water consumption in farming. A single systems combining irrigation and fertilizing will greatly reduce the cost and time needed in farming. There are two types of fertilizers available for home gardener – granular and water-soluble fertilizers. Generally, granular fertilizers release nutrient gradually but can last longer than water-soluble fertilizers. This project will provide an automated system for irrigation and fertilizing for plantation using Arduino as the microcontroller. This system will include a mobile application to control the amount of water during the irrigation and fertilizing processes. The microcontroller communicates with the mobile application via internet using the Wi-Fi modulator. Then, the microcontroller processes the information and operates the irrigation and fertilizing pumps which supplies water and fertilizer through the sprinkler system in the field. Any feedback will be sent to the user through the mobile application.